Análisis multitemporal de la expansión urbana en el municipio de Zipaquirá, Cundinamarca en el periodo 1991-2022 (2023)
The development of this work was carried out a multitemporal analysis of the urban expansion of the municipality of Zipaquirá, Cundinamarca, in this analysis Landsat satellite images of different years were used, which are free to download, the satellite images corresponded to that of the years 1991, 2011 and 2021. To determine the urban areas for each period, a supervised classification of the images was carried out with the Erdas Imagine software, prior to this classification, the pre-processing and readiness of the images was carried out, for which the study area was first determined. , then the multispectral composition was carried out, the images were re-projected to the coordinate systems, the re-scaling where it goes from 16 bit to 8 bit, the study image was cut, finally a spatial improvement was carried out with the tool Pansharpening for Landsat 7 and 8 images and Band 8 that corresponds to the panchromatic image.